Brazilian Labour History in Global Context: Some Introductory Notes. (18th January 2018) - Fontes, Paulo; Fortes, Alexandre; Mayer, David
Abstract: This article introduces the main topics and intellectual concerns behind this Special Issue about Brazilian labour history in global context. Over the last two decades, Brazilian labour history has become an important reference point for the international debate about a renewed labour and working-class history. It has greatly broadened its conceptual scope by integrating issues of gender, race, and ethnicity and has moved towards studying the whole gamut of labour relations in Brazil's history. Furthermore it has taken new perspectives on the history of movements. As background to this Special Issue, this introduction embeds current Brazilian labour historiography in its development as a field and in the country's broader political and social history. Presenting the contributions, we highlight their connections with current debates in Global Labour History.